ISLAMIC RELIGIOUS EDUCATION IN GENERAL UNIVERSITY IN THE POST REFORM ERA - ustadiyah, ustadiyah (Pascasarjana Universitas Wahid hasyim Semarang, 2023)
This study aims to describe and analyze Islamic learning in public universities in the reform era. This research is a qualitative research with the type of case study on Islamic Religious Education in Public Universities. Data collection is done through observation, analysis and document review. The data were analyzed according to the research focus and conclusions were drawn. The results of the study show that firstly, the content of Islamic Religious Education courses at General Colleges consists of three main aspects of Islamic teachings, namely aqidah, sharia and morals with various material developments. Second, strengthening PAI material at PTU in the ecosystem and discourse at PTU. Third, strengthening character in PAI at PTU to produce plus graduate graduates. The implication of this research is to emphasize the importance of revitalizing Islamic Religious Education courses at public universities / PTU both from the materials, methods and evaluation techniques used. Keywords: Islamic Religious Education Course, Public Universities.